44. Onabotulinumtoxin-a treatment in chronic migraine: A long-term prospective open label study. Issue 4 (April 2016) - Butera, C.; Bianchi, F.; Amadio, S.; Guerriero, R.; Cursi, M.; Vimercati, O.; Comi, G.; Carro, U. Del
Abstract : A large multicentre clinical trial (PREEMPT) demonstrated the efficacy and safety of onabotulinumtoxin A for prophylactic treatment of chronic migraine (CM) in prophylactic drug-free patients. This study aimed to verify the efficacy of repetitive injections of onabotulinumtoxin A in CM patients with ineffective chronic poly-therapy. Patients and methods: we studied 45 CM patients (36 females and 9 males) taking multiple prophylactic/symptomatic medications who were treated with onabotulinumtoxin-A for a follow up period of 9 months. The overall dose ranged between 155 and 180 U administered in 31–36 sites following PREEMPT protocol, repeated at 12 weeks intervals. The main evaluated variables to establish drug efficacy included number of headache/migraine days and episodes, total cumulative headache hours, MIDAS and HIT-6 scores; all items were assessed at baseline and after 12–24–36 weeks during follow-up. Results: all variables showed statistically significant changes after 36-weeks time-point. We observed a responder rate (partially responder plus completely responder patients) of about 40% after the first treatment; the rate reached 90% after the third treatment. Adverse events were uncommon and did not require treatment discontinuation. Conclusions: repeated treatments with onabotulinumtoxin A in CM patients with unsatisfactory prophylactic drug treatments, was very effective in improving all variables examined, determining a measurable positive impact on quality of life.